Access, Accountability, and Advocacy: Culturally and Linguistically Diverse Families' Participation in IEP Meetings. Issue 4 (7th August 2020) - Rossetti, Zach; Redash, Amanda; Sauer, Janet S.; Bui, Oanh; Wen, Yuewu; Regensburger, Debra
ABSTRACT: All parents of eligible students with disabilities have the right to collaborate as equal members of educational teams developing their children's Individualized Education Programs (IEP). However, culturally and linguistically diverse families typically experience barriers to collaboration with school professionals. In this paper, we describe findings from four focus group interviews with Chinese, Vietnamese, and Haitian immigrants examining their participation and language access in their children's IEP meetings, as well as their perspectives on what would improve their IEP meetings. Findings revealed that meaningful engagement was hampered by families' limited access to information, educators' lack of accountability, and limited opportunities for families to develop as advocates. Implications of the research addressing the within-meeting and between-meeting barriers are discussed.